Age features of morphological changes of the hematotesticular barrier in experimental diabetes mellitus. - Kondrat, A-I.V.; Zhurakivska, O.Ya. (Морфологія / Morphologia / Morfologìâ, 2021)
Background. Diabetes mellitus is an acute medical and social problem in all parts of the world due to the constant increase in the incidence of the disease, severe complications, disability and high mortality. Hyperglycemia leads to oxidative stress and increased processes of formation of active oxygen species, which in turn make a significant contribution to the development of male infertility. Objective. Therefore, the aim of our study was to establish morphological changes in the vessels of the hemomicrocirculatory flow and testicular sustentocytes of adult rats with experimental streptozotocin diabetes mellitus (SDM). Methods. The material for the study were the testicles of 20 sexually mature 6-month-old rats (weighing 150-180 g). SDM in animals of the experimental group was simulated by a single intraperitoneal injection of streptozotocin (dissolved in 0.1 M citrate buffer solution with a pH of 4.5) at a dose of 6 mg per 100 g of mass. An equivalent dose of 0.1 M citrate buffer was injected intraperitoneally to animals of the control group. Histological, electron microscopic, biochemical, morphometric and statistical research methods were used. Results. It was found that in the early stages of SDM (28th day) on the background of hyperglycemia in the hemomicrocirculatory flow of the testes there is a spasm of the vessels of the afferent link, which is confirmed by a decrease in the lumen of arterioles and an increase in their Wagenworth index. On the 70th day of SDM on the background of elevated levels of glucose and glycosylated hemoglobin in the links of the hemomicrocirculatory flow of the testis there are signs of diabetic microangiopathy, manifested by: hemorheological disorders in micro-hemo-vessels, (erythrocyte sludge, adhesion of erythrocytes and platelets, microclasmatosis), decrease in the capacity of arterioles and capillaries (increase in the Wagenworth index, respectively by 1.8 and 1.9 times), microclasmatosis, thickening and proliferation of the basement membrane of capillaries. Against the background of diabetic microangiopathy, there is a decrease in the number of sustentocytes by 0.01 mm2 of testicular parenchyma by 1.8 times, compared with control indicators, the area of their profile increases by 2.2 times (in all cases p<0.05). The nucleolar areas probably do not change, which leads to an increase in the nuclear-cytoplasmic ratio by 2.9 times (p<0.05). Such morphometric changes of sustentocytes are caused by development of vacuolar hydropic dystrophies in them, and an apoptosis that is confirmed by data of histo-ultrastructural studies. Changes in sustentocytes against the background of the development of diabetic microangiopathy lead to a violation of the hematotesticular barrier and to dystrophic changes in the spermatogenic epithelium of the testis. Conclusion. Thus, on the 70th day of SDM in the hemomicrocirculatory flow of the testis, the development of diabetic microangiopathy is observed, which leads to a violation of the hematotesticular barrier, and as a consequence, to a violation of spermatogenesis.